2006
DOI: 10.1080/08035250500459709
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking during pregnancy and hyperactive-distractible preschooler's: A follow-up study

Abstract: Exposure to tobacco smoke in utero was associated with hyperactive-distractible behaviour in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For instance, Linnet et al reported that smoking in pregnancy increased the prevalence of hyperkinetic disorder by threefold [ 7 ]. Another study [ 8 ] investigated 3.5-year-old preschool children and observed that when compared with children of non-smokers, children born to mothers who smoked 10 or more cigarettes per day had a 60% increased risk of hyperactivity and distractibility. Based on a large, nationally representative sample of children aged 4–11 years, Weitzman et al [ 9 ] suggested an independent relationship between maternal smoking both during and after pregnancy and the increased rates of behavioral problems in children, and their further evidence indicated a dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Linnet et al reported that smoking in pregnancy increased the prevalence of hyperkinetic disorder by threefold [ 7 ]. Another study [ 8 ] investigated 3.5-year-old preschool children and observed that when compared with children of non-smokers, children born to mothers who smoked 10 or more cigarettes per day had a 60% increased risk of hyperactivity and distractibility. Based on a large, nationally representative sample of children aged 4–11 years, Weitzman et al [ 9 ] suggested an independent relationship between maternal smoking both during and after pregnancy and the increased rates of behavioral problems in children, and their further evidence indicated a dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk for intrauterine growth retardation, sudden infant death syndrome, and asthma are well-known adverse effects of in utero tobacco exposure (Higgins 2002). In addition, effects of in utero tobacco exposure on behavioral problems have been reported in various experimental and epidemiologic studies (Ernst et al 2001; Eskenazi and Castorina 1999; Wakschlag et al 2002; Weitzman et al 2002) including some longitudinal studies (Markussen Linnet et al 2006; Wakschlag et al 1997). Prospective studies that systematically assess a broad range of behavioral problems outcomes are sparse.…”
mentioning
confidence: 99%
“…A number of studies have also demonstrated associations between adverse birth outcomes, such as size at birth adjusted for gestational age, and behavioral problems, including hyperactivity/inattention and total behavioral difficulties ( 17 19 ). A separate, but closely related literature has examined the associations between prenatal stress and developmental outcomes of exposed children, and has identified relatively consistent links between various types of maternal stress and child hyperactivity, conduct and peer problems, and behavioral difficulties ( 20 25 ).…”
mentioning
confidence: 99%